Analisis Fluktuasi Jumlah dan Karakteristik Penumpang Bus Trans Jogja Kondisi Sebelum, Selama, dan Setelah Covid-19 - Budi Utomo, Rizki; Winarno, Setya (Teknisia, 2023)
Trans Jogja Urban Public Transportation is a form of reform of the subsidized road transport system in the Special Region of Yogyakarta,  which has served the Yogyakarta Urban Area since 2008. Trans Jogja Buses have served 25 sub-districts, with a fleet of 128 buses subsidized by the DIY Regional Government and 44 buses subsidized by the Ministry of Transportation of the Republic of Indonesia. When the COVID-19 pandemic hit in 2020-2021, there was a decrease in people's movements, resulting in a decrease in Trans Jogja Bus passengers. This study aims to analyze the fluctuations of passengers and compare the characteristics of the Trans Jogja Bus passengers in conditions before COVID-19 (in 2019), during COVID-19 (in 2020 and 2021), and after COVID-19 (in 2022). The analysis results show that based on the monthly average, the number of Trans Jogja Bus passengers in conditions during COVID-19 decreased by 54%. After COVID-19, it increased by 12% compared to during COVID-19.  The monthly average number of passengers After COVID-19 is not as regular as in conditions before COVID-19, with a disparity of 50%t. Based on the characteristics of passengers during COVID-19, the proportion of missing passengers is by the professional aspect, namely students/students and civil servants/national soldiers/police. Regarding travel intentions, a relatively large proportion of the missing were college, school, and tourism travel, each decreasing by 7%.